Seven psalms [compact disc] - Simon, Paul, 1941-; Simon, Paul, 1941- (Legacy Recordings, 2023)
Recorded entirely on acoustic instruments, and performed by Simon, this album showcases Simon's craft at its finest and most captivating, simply with his voice and guitar. Intended to be listened to as one continuous piece, the 33-minute, seven-movement composition transcends the concept of the "album". A stunning, intricately layered work, it's a record which establishes an engaging and meditative, hymnal soundscape, with Simon's lyrics providing the gravitational center for constellations of sound woven from guitar strings and other acoustic instrumentation, including choral elements. True to the origin of psalms as hymns meant to be sung rather than spoken. This album reaches back to the very genesis of folk music King David's Psalms. The result is a quietly moving musical experience which uncovers a wealth of subtle details with every repeated listen. A step apart from anything Paul Simon has released before.